A DFT Perspective on Diels–Alder Organocatalysts Based on Substituted Phosphoramides. Issue 2 (8th November 2018) - Wåhlander, Jakob; Amedjkouh, Mohamed; Balcells, David
Abstract : Phosphoramides are an interesting alternative to the thiourea motif that has long been used in organocatalysis. In the R1 N(H)‐P(O)(R3 )‐N(H)R2 formulation, phosphoramides give the advantage of having a third variable substituent, R3, compared to the two available in thioureas, and the possibility of introducing chirality with an asymmetric phosphorus center. In this work, we present a systematic computational study on the catalytic properties of these underexplored compounds. These studies show the catalytic potential of a series of substituted phosphoramides in Diels–Alder reactions, including the asymmetric [4+2] cycloaddition of pro‐chiral substrates. The nature of the phosphorus‐bound R3 substituent has a significant impact both on catalytic activity and enantioselectivity. Remarkably, several of the phosphoramides studied are predicted to be more active than the Schreiner's thiourea organocatalyst. Abstract : Phosphoramides are explored as an alternative to the thiourea motif in the catalytic Diels–Alder reaction. Computational studies show the high potential of these compounds, with predicted catalytic activities higher than that of Schreiner's thiourea organocatalyst and the possibility of introducing enantioselectivity with a chiral phosphorus center.